BIROKRASI DAN KEBERPIHAKANNYA PADA RAKYAT: Refleksi terhadap Birokrasi ORBA dan Orientasi pada Aplikasi Perspektif Reinventing Government dan Banishing Bureaucracy - Hendrikus Triwibawanto Gedeona (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2005)
Bureaucracy as the government instrument in implementing its functions to deliverdevelopment programs, public services, regulative tasks and people empowerment, has to demonstrate good performance in line with people’s expectation. It must notdemonstrate the culture of paternalism. This means that bureaucracy should actualize people’s expectations, needs, interests, and necessities. It also insinuates that bureaucracy should be able to solve occurring problems in the society. Theperspectives of Reinventing Government and Banishing Bureaucracy may become the alternatives in overcoming the problems. However, in putting the perspectives into practice, we have to filter their values and pick the suitable ones so that the newly modified bureaucracy reflects the actual Indonesian Bureaucracy.